Decisions to imprison : court decision-making inside and outside the law - Wandall, Rasmus H. (Advances in criminology., 2008)
This book presents empirical analyses of the normative and ideological structures of courts' decisions to imprison in the daily handling of criminal cases. It explores the ways in which the courtroom decision-making process upholds decisions as legally valid, whilst at the same time also allows decision-making to reflect wider and more contextual factors.